Disk-Jet Connection - Vlahakis, N. (2006)
AGN jets are collimated, relativistic flows that emanate from accretion disks around supermassive black holes. Electromagnetic stresses are the most plausible candidate for extracting energy at the source and converting it into outflow kinetic energy. Among the questions that need to be answered in order for these processes to be well understood are: How the conditions near the disk are related to the terminal Lorentz factor of the jet? What is the asymptotic value of the Poynting-to-matter energy flux ratio? Can we explain the apparent kinematics of the observed jet components? I present exact solutions as well as a general analysis of the ideal magnetohydrodynamic equations that help to shed light on these questions.